Improved generation wind power dispatch management system - CHEN XIANGANG (2017)
The utility model provides an improved generation wind power dispatch management system, including apron, sealing strip, observation window, alarm, casing, scheduling controller, the wiring groove, the drier, the bleeder vent, the dust screen, dispatch record table, the schedule monitoring ware, equipment data analysis unit, the dispatch analytic unit, dispatch safety analysis unit, identity recognition device and pickproof lock, the apron edge paste the sealing strip, apron central authorities set up the observation window. The utility model discloses scheduling controller, the wiring groove, equipment data analysis unit's setting is favorable to optimizing management system, reduces administrative cost, decreasing failure rate, guarantee fail safe nature, be convenient for marketing and application. 本实用新型提供种改进型电力调度管理系统，包括盖板，密封条，观察窗，报警器，壳体，调度控制器，接线槽，干燥剂，透气孔，防尘网，调度记录表，调度监控器，设备数据分析单元，调度分析单元，调度安全分析单元，身份识别装置和防盗锁，所述的盖板边缘粘贴密封条；所述的盖板中央设置观察窗。本实用新型调度控制器，接线槽，设备数据分析单元的设置，有利于优化管理系统，降低管理成本，降低故障率，保障安全可靠性，便于市场推广和应用。